PENGARUH KEIMANAN TERHADAP KETAHANAN MENTAL DI KALANGAN REMAJA - Khairunnisa Khairunnisa; Risma Dhia Rohadatul Aisy; Sheila Hariry (Kampus Akademik Publiser, 2025)
Mental health issues among adolescents are increasingly receiving attention, along with the increasing social, academic, and identity crisis pressures that they often experience. Faith, as a form of spiritual strength, is believed to be a protective factor in dealing with these life pressures. This study aims to examine the relationship between faith and mental resilience in adolescents through a literature study approach. The literature analyzed shows that adolescents who have a high level of faith tend to be more emotionally stable, able to manage stress, and have a more positive outlook on life. Religious activities such as reading the Qur'an, praying, and dhikr have been shown to provide a psychologically calming effect and strengthen the ability to adapt to life's pressures. Thus, faith not only functions as a religious expression, but also has the potential to be a supporting strategy in maintaining adolescent mental health. This study recommends the need for synergy between spiritual, psychological, and educational approaches in fostering the mental resilience of the younger generation.